Enhanced durability of styrene butadiene rubber nanocomposite using multifunctionalized titanium dioxide. (16th February 2016) - Park, Kwang Hyun; Kim, Jungmo; Kwon, O‐Seok; Lee, Dongju; Kim, Jin; Yoon, Hyewon; Ahn, Changui; Song, Sung Ho
Abstract : Homogeneous and stable dispersion of nanoparticles in polymer matrix remains a significant challenge. Here, we propose a simple and effective route for synthesizing functionalized TiO2 nanoparticles through oleic acid. The Oleic‐TiO2 nanoparticles homogeneously dispersed in SBR matrix show remarkable improvement of mechanical properties such as modulus, tensile strength, and fatigue properties, even at low loadings, which are ascribed to the enhanced interfacial bonding with the polymer matrix. Moreover, the incorporation of the Oleic‐TiO2 into SBR matrix significantly prevents photo and thermal degradation. Therefore, we confirm that our approach can suggest fascinating potentials to be scalable and commercial in polymer engineering. POLYM. COMPOS., 38:E174–E180, 2017. © 2016 Society of Plastics Engineers